The Age of Criminal Responsibility in Children: some of Islamic Views - Mohammad Rasool Ahangaran (International Journal of Pediatrics, 2015)
The age of criminal responsibility of children in the Islamic Penalties Act has been determined as religious Bulugh (puberty) Nasab. According to this, criminal authorities hold girls criminally liable and punishable at 9 complete lunar years and boys at 15 complete lunar years. Unfortunately, our legislator has set criminal responsibility of children based on sexual maturity; therefore, thousands of newly born infants who are unable to think have been liable to punishment, while in the realization of criminal responsibility there is a need for intellectual maturity (growth) in addition to sexual maturity; that is, in the realization of criminal responsibility of children, there are two necessary conditions: “attainment of puberty boundary” and “achieving growth and attainting intellectual maturity”; otherwise, the child has no criminal responsibility and we cannot hold him liable for his action and punish him. In this research, an attempt is made to address the problems of the Act by drawing on the Islamic sources.